Detection of pyrazinamide resistance among multidrug resistant tuberculosis in North Karnataka - Dhapalapur, Nivedita R.; Nirmala; Hegde M., Archana (International Journal of Research in Medical Sciences, 2025)
Background: Pyrazinamide was identified as a result of a structural activity connection with nicotinamide, which exhibits antitubercular properties (PZA). PZA possesses the exceptional capacity to be directly identified in vivo, first in Mycobacterium TB-infected mice and guinea pigs and subsequently in clinical settings. Pyrazinamide (PZA) is a newly developed antituberculosis (anti-TB) medication that is necessary to shorten the duration of TB treatment. Drug-resistant and drug-susceptible TB, including multidrug-resistant TB, require PZA as part of any therapy regimen because it eliminates nonreplicating persisters that other TB treatments are unable to. Methods: All clinical specimens presented to the centre for follow-up or for newly diagnosed cases requiring programmatic treatment of DRTB were included in the research. Salivary or insufficient samples, as well as samples that satisfied the centre’s SOP rejection criteria, were excluded from the research. MGIT-based susceptibility testing was used to evaluate the PZA susceptibility for 609 isolates. Results: Of the 11104 samples, 207 (1.8%) were identified as MDR, 101 (0.9%) as mono-rifampicin resistant, and 619 (5.5%) as mono-isoniazid resistant. The BACTECTM MGITTM 960 technique was then used to cultivate 609 samples. The Bioline TB Ag MPT64 test is a quick way to find the M. tuberculosis complex. PZA susceptibility for 609 isolates was assessed using MGIT-based susceptibility testing. PZA resistance was detected in 194 (31.8%) of the 609 isolates. Conclusions: The results may emphasise the necessity of regular DST for PZA in Indian public health labs and more study to better identify the variables linked to PZA resistance. In order to inform evidence-based approaches for tuberculosis control and care, this study also highlights the significance of ongoing surveillance of medication resistance patterns.